2017
DOI: 10.3389/fvets.2017.00136
|View full text |Cite
|
Sign up to set email alerts
|

A Stakeholder Survey on Live Bird Market Closures Policy for Controlling Highly Pathogenic Avian Influenza in Vietnam

Abstract: Extensive research in Vietnam and elsewhere has shown that live bird markets (LBMs) play a significant role in the ecology and zoonotic transmission of avian influenzas (AIs) including H5N1 and H7N9. Vietnam has a large number of LBMs reflecting the consumer preferences for live poultry. Under pressure to mitigate risks for H7N9 and other zoonotic AIs, Vietnam is considering, among other mitigation measures, temporary closures of LBMs as a policy to reduce risk of AI outbreaks. However, the efficacy of market … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
(36 reference statements)
0
15
0
Order By: Relevance
“…Some owners also believed that the vaccine was not tested rigorously enough due to it being developed in in a rush, which has been identified in other human behavioral studies as yet another reason why people may fail to adopt vaccinations ( 14 ). Regarding other dynamic human behaviors, empirical observations suggest that live bird market closures in response to avian influenza outbreaks may induce an undesirable behavioral change in poultry owners, such as increasing the frequency of movements of high-risk animals to avoid culls or performing illegal trading through an underground markets ( 15 , 16 ) both of which contribute to further disease spread ( 17 ). Other studies have similarly reported that movement restrictions can result in infected livestock being sold from an area where disease outbreak occurs ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some owners also believed that the vaccine was not tested rigorously enough due to it being developed in in a rush, which has been identified in other human behavioral studies as yet another reason why people may fail to adopt vaccinations ( 14 ). Regarding other dynamic human behaviors, empirical observations suggest that live bird market closures in response to avian influenza outbreaks may induce an undesirable behavioral change in poultry owners, such as increasing the frequency of movements of high-risk animals to avoid culls or performing illegal trading through an underground markets ( 15 , 16 ) both of which contribute to further disease spread ( 17 ). Other studies have similarly reported that movement restrictions can result in infected livestock being sold from an area where disease outbreak occurs ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…PVC types 1-5 are the traditional and yet more common chains, while type 6 and type 7 are modern chains arranged by private companies; and type 9 and type 10 are incomplete chains as part of the chain is organized outside the country, and they are responsible for only a small proportion of pig production in the country. Similar to chicken and beef value chains, the PVCs in Vietnam are flexible due to the presence of traders in the chains (Nguyen et al 2017). The amount of pork consumed in Vietnam is 2.5 and 5 times higher than the poultry and beef consumption (Nguyen and Ngo 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The economic context of poultry farming in some endemic countries is favorable to depopulation in response to disease infection: chick and finished poultry are traded with limited equipment (motorcycle for transportation, storage of poultry at home or in enclosures of live bird markets) (29–31) which limits transaction costs associated with the sale and replacement of flocks. Moreover, the limited sanitary controls and flexibility of the trade networks allow the sale of sick and/or young birds and their use for human consumers or by other livestock farms (python, crocodile, fish) (6, 15, 32–35). The depopulation behavior can explain why avian influenza viruses of the H5 subtype are more likely isolated from poultry sampled in live bird markets (34, 36, 37) than in poultry farms (38–40).…”
Section: Discussionmentioning
confidence: 99%